Análise da frequência espectral na avaliação do controle postural em tarefas simples e de dupla tarefa em adultas-jovens e idosas - Prusch, Samuel Klippel (2021)
The postural control system is based on three distinct sensory systems, namely the vestibular, visual and somatosensory systems. These systems send information via afferent routes to the Central Nervous System, which emits motor responses, via efferent routes, to preserve the maintenance of postural control. Body oscillation is widely studied, mainly by traditional evaluations, which use the oscillation of the Pressure Center (COP), on the individual's support base. However, there is an evaluation of the sensory systems, which takes place through a frequency analysis. In this evaluation it is possible to identify which frequency bands in which each system would act more, in each situation. In view of this, the objective of this study is to compare postural control in single and double tasks in young-adult and elderly women, through the analysis of the spectral frequency. The study consisted of a group of elderly women (IG), with 16 participants and a group of young adults, composed of 17 participants (GJ). In this evaluation, a force platform was used for the acquisition of postural control data in simple tasks (eyes open and eyes closed) and in double task (Laser test - elliptical task with the right hand (CIRD) left (CIRE), horizontal right (HORD) and left (HORE) task, memory test (MEM) and Stroop test (ST). The variables in the spatio-temporal domain evaluated were anteroposterior COP displacement amplitude (COPap), amplitude of mediolateral displacement of the COP (COPml), average displacement speed of the COP (COPvm) and oscillation area of the COP (COPsa). For the analysis in the frequency domain, the medians of the frequencies present in the signals of the COP were used, in the anteroposterior directions. posterior and mediolateral. The data were submitted to descriptive statistics. The normality in the distribution of the data was verified through the Shapiro-Wilk test, the homogeneity through the Levene test.In the analysis of the COP for normal data it was used t test for independent samples was used. For non-normal data, the Mann-Whitney test was used for comparisons. For the frequency analysis, the numerical values were transformed into categorical, divided according to the frequency bands, being classified as low (0 - 0.7 Hertz), medium (0.7 - 1 Hertz) and high (1 - 3 Hertz). Then, a cross-reference table test was performed, with analysis of the Chi-square test and Fischer test, when necessary. The level of significance for all tests was 5%. The analysis of the COP showed that dual task situations affect the postural control of the elderly, in relation to the group of young people. Through the frequency band analysis, the results pointed to sensory changes mainly in the mediolateral direction, even within the test itself (in the intervals from 0s to 10s, 10s to 20s and 20s to 30s). Furthermore, from the results found, it is worth mentioning that although there is no difference in the COP variables for the OA and OF situations, in the evaluation of the frequencies, differences were found in the sensory strategies between the groups.